Total Hardness Test on Dug Well Water in Alak Village, Kupang City - Christine J K Ekawati; Byantarsih Widyaningrum (Postgraduate, University of Mataram, 2023)
Total hardness is the content of Ca2+, Mg 2+ and other 2-valent ions in clean water and drinking water. The hardness level of dug well water in Alak Village is high. The purpose of this study was to determine the total hardness content of dug well water in Alak Village, Kupang City. The research method is pre-experimental with a research design that is cross-sectional study. The results showed that the results of the Total Hardness measurement of the 20 dug wells, the largest was 548 mg/L and the lowest was 384 mg/L. The average result of Total Hardness measurement is 466.20 mg/L. It is suggested for the health center in Alak Village to be able to provide education about the negative impact of Total Hardness which reaches above 500 mg/L.